Doping‐induced coloration in titania. Issue 7 (6th April 2021) - Mane, Rahul B.; Sahoo, Ramkrishna; Reddy, Bapathi Kumaar Swamy; Ravula, Vijay; Panigrahi, Bharat B.; Borse, Pramod H.; Chakravarty, Dibyendu
Abstract: Thermal decomposition of Ti3 GeC2 MAX phase at 1773 K yields an orange‐colored titania powder. Micro‐XRD of the powder under oscillation mode reveals a pure rutile phase ( space group P42/ mnm ). X‐ray photoelectron spectroscopy confirmed substitutional doping of Ge in the titania lattice. The presence of Ti‐O‐Ge bond was observed in O 1s spectrum and confirmed by the shift in binding energy in Ti 2p3/2 and Ge 3d peaks. The UV‐visible Diffuse Reflectance Spectrum studies on the Ge‐doped titania powder show wide absorption in the visible region (380 to 650 nm) yielding a bandgap of 2.83 eV, which is desirable for photocatalytic applications. Defect states formed due to Ge doping led to lowering of the titania conduction band inducing an orange coloration in the powder.